Effectiveness of Cash Management System (CMS) in Improving the Performance of Expenditure Treasurers - Anggia, Sofina; Mutmainah, Siti; Salapudin, Salapudin (International Journal of Economics Development Research (IJEDR), 2024)
Digitalization has brought transformation in financial transactions. The presence of CMS as a government non-cash payment system also plays a role. Expenditure treasurers must adapt quickly to improve performance, especially in cash management. However, the realization of its implementation until 2023 is still low. Findings regarding cash management at the expenditure treasurer also continue to be repeated. Therefore, this research was conducted to see how effective CMS is in improving treasurer performance. The aspects evaluated include human resources, procedures and instructions, IT infrastructure and systems, data and security controls. This concept is explained through the Technology of Acceptance Model (TAM) and Accounting Information System (AIS). Analysis using SmartPLS concluded that all components, procedures and instructions still need to be improved, even though all components are working well overall. The effectiveness of CMS has a positive effect on the performance of the expenditure treasurer. Expenditure treasurers must be motivated to be consistent in their use so that cash management becomes transparent and accountable. Providers of goods and services also need to be encouraged to provide non-cash payment modes.